2019
DOI: 10.1002/jclp.22882
|View full text |Cite
|
Sign up to set email alerts
|

Hope, optimism, self‐efficacy, and posttraumatic stress disorder: A meta‐analytic review of the protective effects of positive expectancies

Abstract: Objective The present meta‐analysis consolidated research examining how positive expectancies (e.g., hope, self‐efficacy, and optimism) may protect against the development of posttraumatic stress disorder (PTSD). Method Articles were identified by searching PILOTS, PsycINFO, PubMed, and ProQuest Dissertations and Theses databases. Results Aggregated results from 154 studies indicated that positive expectancies were associated with lower levels of PTSD symptoms. This relationship was stronger for coping‐specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
97
4
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 223 publications
15
97
4
13
Order By: Relevance
“…), we found that self‐efficacy routinely displayed a statistically significantly stronger association with other measures of goal‐related cognition and with symptoms of psychopathology compared to hope and grit. The relative strength of associations between self‐efficacy and these variables in our study aligns with prior findings documenting statistically significant inverse relations between self‐efficacy and symptoms (Gallagher et al, 2020; Maddux & Kleiman, 2016; Muris, 2002; Volz et al, 2019) and self‐efficacy and success across a wide variety of life domains (Bandura & Locke, 2003). Our study extends these results by comparing the strength of the relations with self‐efficacy to two related but distinct constructs, namely grit and hope.…”
Section: Discussionsupporting
confidence: 90%
“…), we found that self‐efficacy routinely displayed a statistically significantly stronger association with other measures of goal‐related cognition and with symptoms of psychopathology compared to hope and grit. The relative strength of associations between self‐efficacy and these variables in our study aligns with prior findings documenting statistically significant inverse relations between self‐efficacy and symptoms (Gallagher et al, 2020; Maddux & Kleiman, 2016; Muris, 2002; Volz et al, 2019) and self‐efficacy and success across a wide variety of life domains (Bandura & Locke, 2003). Our study extends these results by comparing the strength of the relations with self‐efficacy to two related but distinct constructs, namely grit and hope.…”
Section: Discussionsupporting
confidence: 90%
“…Belief in the ability to cope (such as reminding yourself of your capacity for resilience) and youth’s beliefs in their own capacity to cope in a healthy way were weakly correlated with PTSD symptoms [ 12 ]. Scholars have consistently found that coping self-efficacy is associated with lower rates of PTSD in trauma-affected children and adolescents [ 77 , 78 ]. Unfortunately, few studies in the reviewed articles incorporated measures of coping self-efficacy, and those that did, did not include additional measures examining coping styles or strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we may think of hope as a potentially relevant resiliency factor in the context of the COVID-19 pandemic as it may facilitate continued goal pursuit despite difficult circumstances. Indeed, extant research has demonstrated negative relations between hope and anxiety across samples (e.g., Arnau et al, 2007;Gana et al, 2013), including prospective effects on symptoms of PTSD in meta-analytic reviews (Gallagher, Long, & Phillips, 2020).…”
Section: Introductionmentioning
confidence: 99%